Measuring the real size of the world economy : the framework, methodology, and results of the international comparison program - ICP (World Bank Washington DCUS, 2013)
Provides a comprehensive review of the statistical theory and methods underlying the estimation of PPPs and real expenditures, the choices made for the 2005 ICP round, and the lessons learned that led to improvements in the 2011 ICP. Contains several chapters about uses of the data from the 2005 ICP.
Keywords: PURCHASING POWER